Pengungkapan tanggung jawab sosial perusahaan, likuiditas, dan keterbandingan laporan keuangan terhadap kinerja keuangan - Hasibuan, Ernita; Syahzuni, Barlia Annis (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
This study aims to analyze the effect of corporate social responsibility, liquidity, and comparability of financial statements on financial performance partially. This research is quantitative research. The object of this research is food and beverage sector companies listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling with the number of samples used as many as 14 companies with the observation period 2018-2021. This study uses multiple linear regression analysis methods, which are processed using SPSS statistical data processing software. it is concluded that the GRI index social responsibility does not have a significant impact on the financial performance of the food and beverage sector. Liquidity proxied by the current ratio is a variable that has a significant positive effect on the financial performance of the food and beverage sector. While the comparability of financial statements proxied by stock returns partially has no significant impact on financial performance in the food and beverage sector.